Spatiotemporal Evaluation of Pulmonary Tuberculosis Case in Karang Intan District, South Kalimantan, 2020-2021 - Hadrianti Haji Darise Lasari; Amelia Amelia; Rudi Fakhriadi; Dian Rosadi; Musafaah Musafaah; Indra Haryanto Ali (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Pulmonary Tuberculosis, hereinafter abbreviated as pulmonary TB, is an infectious disease caused by a group of acid-resistant bacteria, namely Mycobacterium tuberculosis. Pulmonary TB is also still a major health problem in Banjar District, South Kalimantan Province, Indonesia. This research is a descriptive study that aims to identify spatial and temporal clusters of pulmonary TB cases in Karang Intan District, Banjar Regency during 2020 – 2021. The statistical retrospective space-time scan with a Poisson probability model was performed to analyzed the data. The spatial units analyzed in this study included 26 villages in Karang Intan District, with a time unit of 2 years, namely 2020 – 2021. The results of the analysis show that there were 3 clusters of pulmonary TB detected and spread across 26 villages in Karang Intan District. There were 2 clusters in 2020, and 1 cluster in 2021. The transmission of pulmonary TB clusters during 2020-2021 was mostly found in areas with relatively medium or high population density. However, the three detected clusters show a P-value > 0,05 which indicates that the clusters are not statistically significant.